2017
DOI: 10.1111/petr.13019
|View full text |Cite
|
Sign up to set email alerts
|

Oral health of pediatric liver transplant recipients

Abstract: To evaluate oral health conditions in pediatric liver transplant recipients, with special focus on caries, green staining of the teeth, gingival bleeding, and gingival overgrowth. 40 patients (mean age 11.6 years) were examined at a routine follow-up visit, 6 months to 16 years after liver transplantation at the Swiss Center for Liver Disease in Children. After the medical examination, participants were further examined for the presence of dental caries, periodontal disease, GE, and GTC. The mean decay, missin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…All of the liver transplant patients enrolled into the study were placed on tacrolimus therapy either exclusively or in combination with mycophenolate mofetil, which has not been associated with gingival hyperplasia. Although, some studies have concluded that a lack of gingival enlargement is associated with tacrolimus [10,24], a finding similar to ours was reported by Sandoval et al [25]. They identified gingival enlargement in 7 out of 40 pediatric patients (18%) taking tacrolimus [25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All of the liver transplant patients enrolled into the study were placed on tacrolimus therapy either exclusively or in combination with mycophenolate mofetil, which has not been associated with gingival hyperplasia. Although, some studies have concluded that a lack of gingival enlargement is associated with tacrolimus [10,24], a finding similar to ours was reported by Sandoval et al [25]. They identified gingival enlargement in 7 out of 40 pediatric patients (18%) taking tacrolimus [25].…”
Section: Discussionsupporting
confidence: 89%
“…Although, some studies have concluded that a lack of gingival enlargement is associated with tacrolimus [10,24], a finding similar to ours was reported by Sandoval et al [25]. They identified gingival enlargement in 7 out of 40 pediatric patients (18%) taking tacrolimus [25]. Also, a slightly higher percentage (25%) was previously reported by Shiboski et al [6].…”
Section: Discussionsupporting
confidence: 89%
“…Changes affecting soft and hard tissues of the oral cavity are among the most widespread changes. The most common oral changes include gingival enlargement, periodontal diseases, desquamation of the oral epithelium, very painful ulcerations, polypoid and granulomatous changes in the oral mucosa and in the later stages, also occurrence of oral cancer [2,3]. Due to the extensive accumulation of oral biofilm and the presence of mineralized deposits on the teeth, these patients are also suffering from diseases of hard tooth tissues with frequent complications.…”
Section: сажетакmentioning
confidence: 99%
“…Dental care: dental care is often overlooked in the liver transplant recipient [ 40 , 41 ]. Many patients with liver disease have dental problems and these may be exacerbated post-transplant.…”
Section: Follow-up Of Transplant Recipientsmentioning
confidence: 99%
“…Those transplanted for autoimmune liver diseases may also have sicca syndrome which is associated with dental problems. In one study of 40 paediatric liver allograft recipients in Switzerland, just under half presented at least one carious lesion and two-thirds had more than 20% of sites with plaque and gingival inflammation [ 41 ]. Gingival hypertrophy is associated especially with use of cyclosporin and some other drugs as nifedepine.…”
Section: Follow-up Of Transplant Recipientsmentioning
confidence: 99%